Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ra01296e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of boron-doped ordered mesoporous carbons as efficient electrocatalysts for the oxygen reduction reaction

Abstract: Boron-doped OMCs with a high doping content of 1.17 wt% show excellent catalytic performance for ORR in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In contrast to N, B possesses lower electronegativity (~ 2.04) than C (~ 2.55) [54], and if doped to carbon, B becomes an electron acceptor, inducing a positive charge and resulting in charged sites (B + ) that favor O 2 adsorption and thus increased ORR activity [55,56]. To study the important effects of B-doping and to create sufficient active sites, researchers [54,57,58] have focused their attention on combining mesoporous carbon structures with B-doping to explore advanced metal-free carbon catalysts. For example, Shu et al [57] prepared novel mesoporous boron-doped onion-like carbon (B-OLC) microspheres using nanodiamond and boric acid as C and B sources for rechargeable sodium-oxygen (Na-O 2 ) batteries.…”
Section: Other Heteroatom-doped Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to N, B possesses lower electronegativity (~ 2.04) than C (~ 2.55) [54], and if doped to carbon, B becomes an electron acceptor, inducing a positive charge and resulting in charged sites (B + ) that favor O 2 adsorption and thus increased ORR activity [55,56]. To study the important effects of B-doping and to create sufficient active sites, researchers [54,57,58] have focused their attention on combining mesoporous carbon structures with B-doping to explore advanced metal-free carbon catalysts. For example, Shu et al [57] prepared novel mesoporous boron-doped onion-like carbon (B-OLC) microspheres using nanodiamond and boric acid as C and B sources for rechargeable sodium-oxygen (Na-O 2 ) batteries.…”
Section: Other Heteroatom-doped Carbonsmentioning
confidence: 99%
“…To obtain optimal bifunctional catalysts, an important comparison of the different types of heteroatom-doping was conducted by Su et al [58], in which N, B, and P were used to dope ordered mesoporous carbons (OMCs). The researchers found that improvements to charge transfer kinetics is strongly depended on the nature of the doped heteroatom.…”
Section: Other Heteroatom-doped Carbonsmentioning
confidence: 99%
“…Su et al. reported a facile approach for the synthesis of a series of boron‐doped ordered mesoporous carbon with different B content . The B doping significantly enhances the ORR activity in alkaline media; in particular, a carbon material with 1.17 wt % B dopant showed an optimum ORR activity.…”
Section: Bifunctional Oxygen Catalystsmentioning
confidence: 99%
“… 20 For example, adding nitrogen dopants that have higher electronegativity will generate positive charge density on carbon atoms and the O 2 chemisorption will change, which in turn will also effectively weaken the O–O bond and thereby promote the ORR. 21 Most commonly used heteroatoms for carbon doping are nitrogen, 20 , 22 boron, 23 , 24 sulfur, 25 , 26 and phosphorus. 27 , 28 Special focus has lately been directed to nitrogen-doped carbon as ORR catalysts, as interest in this topic has grown considerably.…”
Section: Introductionmentioning
confidence: 99%